Introduction to the Workflow Systems in Management - Aleksander Wocial (Contemporary Economics)
The article concerns ontology of workflow management systems. The fundamental diagrams and their constituent elements are presented, the meaning of components and relation or interaction among them as well. The first is conceptual model of flow process, followed by meta model of process definition. The understanding of terms is crucial for IT or management specialists involved in the area of workflow.